The renal blood flow reserve in healthy humans and patients with atherosclerotic renovascular disease measured by positron emission tomography using [O-15]H2O - Paivarinta J; Koivuviita N; Oikonen V; Iida H; Liukko K; Manner I; Loyttyniemi E; Nuutila P; Metsarinne K (SPRINGER HEIDELBERG, 2022)
Background: Microvascular function plays an important role in ARVD (atherosclerotic renovascular disease). RFR (renal flow reserve), the capacity of renal vasculature to dilate, is known to reflect renal microvascular function. In this pilot study, we assessed PET (positron emission tomography)-based RFR values of healthy persons and renal artery stenosis patients.Seventeen patients with ARVD and eight healthy subjects were included in the study. Intravenous enalapril 1 mg was used as a vasodilatant, and the maximum response (blood pressure and RFR) to it was measured at 40 min. Renal perfusion was measured by means of oxygen-15-labeled water PET. RFR was calculated as a difference of stress flow and basal flow and was expressed as percent [(stress blood flow - basal blood flow)/basal blood flow] x 100%.Results: RFR of the healthy was 22%. RFR of the stenosed kidneys of bilateral stenosis patients (27%) was higher than that of the stenosed kidneys of unilateral stenosis patients (15%). RFR of the contralateral kidneys of unilateral stenosis patients was 21%. There was no difference of statistical significance between RFR values of ARVD subgroups or between ARVD subgroups and the healthy. In the stenosed kidneys of unilateral ARVD patients, stenosis grade of the renal artery correlated negatively with basal (p = 0.04) and stress flow (p = 0.02). Dispersion of RFR values was high.Conclusions: This study is the first to report [O-15]H2O PET-based RFR values of healthy subjects and ARVD patients in humans. The difference between RFR values of ARVD patients and the healthy did not reach statistical significance perhaps because of high dispersion of RFR values. [O-15]H2O PET is a valuable non-invasive and quantitative method to evaluate renal blood flow though high dispersion makes imaging challenging. Larger studies are needed to get more information about [O-15]H2O PET method in evaluation of renal blood flow.